2023
DOI: 10.15359/ru.37-1.17
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of ethanolic plant extracts on Aedes aegypti larvae

Abstract: [Objective] The objective of this study was to determine the larvicidal activity against A. aegypti of ethanolic extracts of plants commonly found in Costa Rica. [Methodology] Larvicidal activity of ethanolic extracts of plants was determined in this study using the WHO/VBC/81.807: WHO/VBC/81. from 1981. An analysis PROBID for dose response was conducted to determine LC50 of the most prominent extracts. [Results] A total of six extracts with the highest toxicity were chosen, with the stem extract of Ipomoea ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…[19][20] Therefore, it is concluded that the extract of H. riparia leaves was the most efficient for controlling A. aegypti populations, so they deserve to be studied in depth given their potential larvicidal effect. Similar results were obtained by Alvarez-Valverde et al (2023) [29] when they applied powdered leaves of Ipomoea cairica on having the lowest LC 50 of 0.0341 mg/mL offered to A. aegypti, arguing that the differences were due to the protection that the wheat grain provided to the insect. The insecticidal effect produced by the EE of H. riparia on III and IV instar larvae of A. aegypti is associated with the toxicity caused by the phytochemicals of the extract, which could induce starvation and suffocation of the insect.…”
Section: Discussionsupporting
confidence: 85%
“…[19][20] Therefore, it is concluded that the extract of H. riparia leaves was the most efficient for controlling A. aegypti populations, so they deserve to be studied in depth given their potential larvicidal effect. Similar results were obtained by Alvarez-Valverde et al (2023) [29] when they applied powdered leaves of Ipomoea cairica on having the lowest LC 50 of 0.0341 mg/mL offered to A. aegypti, arguing that the differences were due to the protection that the wheat grain provided to the insect. The insecticidal effect produced by the EE of H. riparia on III and IV instar larvae of A. aegypti is associated with the toxicity caused by the phytochemicals of the extract, which could induce starvation and suffocation of the insect.…”
Section: Discussionsupporting
confidence: 85%